TWO-AXIS SOLAR PANEL TRACKING DEVICE PROTOTYPE WITH IOT-BASED MONITORING - Awan, M. Asep Rizkiawan; Sofwan, Agus Sofwan; Multi, Abdul (International Journal Science and Technology, 2024)
The aim of this project is to develop a dual-axis solar tracker equipped with an IoT monitoring system with the BLYNK platform using Arduino. Overall, solar energy refers to technologies that generate power from sunlight. The utilization of solar energy has been around for centuries and has been widely used without relying on other energy supplies. However, its importance is increasing as environmental awareness grows and the availability of other energy sources, such as fuel, becomes limited. Sun tracking systems are an effective technology that can improve the efficiency of solar panels by following the movement of the sun. With the help of this system, solar panels can automatically orient themselves to sunlight, improve sunlight detection, and increase electricity collection because solar panels can always be in a bright position. This project focuses on developing a two-axis sun tracker using Arduino Uno as the main controller. For its implementation, four light-sensitive resistors (LDRs) are used to detect sunlight and maximum light intensity. Two servo motors are used to move the solar panel according to the direction of sunlight detected by the LDRs. Furthermore, an ESP8266 WIFI device is used as an intermediary between the device and the IoT monitoring system. The IoT monitoring system is a website that serves to store data. The efficiency of this system is tested and compared with single axial sun tracking. The results show that the two-axis solar tracking system generates more power, voltage, and current compared to the single axial solar tracker.